Minimal residual disease status predicts outcomes in patients with follicular lymphoma treated with chemo-immunotherapy on the SWOG S0016 trial - Alexey V. Danilov; Hongli Li; Mazyar Shadman; Lisa Rimsza; Ahmad Zebari; Sonali M. Smith; Michael LeBlanc; Jonathan W. Friedberg; Christopher Carlson; Joo Y. Song (Haematologica, 2025)
Not available.